Safety assessment of the insecticidal protein IPD079Ea from the fern, Ophioglossum pendulum. (August 2022) - Carlson, Anne B.; Mathesius, Carey A.; Ballou, Stephen; Fallers, Melissa N.; Gunderson, Tim A.; Hession, Aideen; Mirsky, Henry; Stolte, Brian; Zhang, John; Woods, Rachel M.; Herman, Rod A.; Roper, Jason M.
Abstract: As agricultural biotechnology continues to develop solutions for addressing crop pests through newly expressed proteins from novel source organisms, with different modes or sites of action and/or different spectra of activity, the safety of these proteins will be assessed. The results of hazard-identification and characterization studies for the insecticidal protein IPD079Ea, which is derived from a fern ( Ophioglossum pendulum ) and active against the maize pest western corn rootworm ( Diabrotica virgifera virgifera, Coleoptera: Chrysomelidae) are provided. Collectively these results indicate that IPD079Ea is unlikely to present a hazard to human or animal health and support the safety of genetically modified maize expressing IPD079Ea. Highlights: IPD079Ea is a novel insecticidal protein derived from Ophioglossum pendulum. IPD079Ea offers a new site of action to protect against WCR in GM maize. IPD079Ea protein safety was assessed through a weight-of-evidence approach. No IPD079Ea protein toxin or allergen hazard was identified. IPD079Ea is unlikely to be a hazard to human or animal health.